Laws that administrator in tertiary institution should know in prevention of drugs, alcohol and substance abuse - Kamarudin, Abdul Rani; Mos, Md (2014)
The Ministry of Education Malaysia (formerly known as Ministry of Higher Education) has come out with a Guideline on the Prevention of Drugs, Alcohol and Substance Abuse. This is in accordance with the Malaysian Government Policy to be free from dangerous drugs abuse in higher education by 2015. Consistent and in addition with the Guideline, this paper aims to discuss the relevant policies, laws, rules and regulations that administrators in tertiary institution are expected to familiarise themselves with and for them to take the necessary intervention measures. With regard to the intervention measures, the relevant administrators must be mindful of the relevant policies, laws, rules and regulations that apply to their respective institution or entity. In this paper, how those laws such as Universities and University Colleges Act 1971 (Act 30), Private Higher Educational Institutions Act 1996 (Act 555), Universiti Teknology Mara Act 1976 (Act 173), Education Act 1996 (Act 550) and Statutory Bodies (Discipline and Surcharge) Act 2000 (Act 605) apply are explained. Integral to the above laws, the importance of investigation and chain of custody and evidence, the basic principles of natural justice will also form part and parcel of the discussions especially when disciplinary action against the student or staff members is initiated.